2012
DOI: 10.17660/actahortic.2012.927.46
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salinity and Boron Excess on the Growth, Photosynthesis, Water Relation and Mineral Composition of Laurustinus Grown in Greenhouse

Abstract: A greenhouse study was conducted to determine the interactive effects of NaCl salinity and boron on the growth, plant water status, gas exchange, chlorophyll fluorescence and concentrations of sodium (Na), chloride (Cl) and boron (B) in laurustinus (Viburnum tinus L.). Potted plants were grown in a factorial combination of salinity (2 and 6 dS m -1 ) and boron (1 and 6 mg L -1 ). Plant dry weight (DW) decreased with salinity and B excess, particularly as a result of the former. The salinity × B interaction on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Viburnum lucidum had 54% and 48% less leaf number and leaf area, respectively, when irrigated with 200 mM NaCl solution compared with the control (0 mM NaCl) (Cirillo et al, 2016). Bañ on et al (2012aBañ on et al ( , 2012b found that 24% of leaves abscised and leaf area decreased by 48% when V. tinus (laurustinus viburnum) was irrigated with saline solution at an EC of 6.0 dS • m -1 compared with the control (2.0 dS • m -1 ). Callistemon citrinus (red bottlebrush) had a reduction in leaf area of 12% when irrigated with 44 mM NaCl solution (4.0 dS • m -1 ) compared with the control (0.8 dS • m -1 ) ( Alvarez and S anchez-Blanco, 2014).…”
mentioning
confidence: 99%
“…Viburnum lucidum had 54% and 48% less leaf number and leaf area, respectively, when irrigated with 200 mM NaCl solution compared with the control (0 mM NaCl) (Cirillo et al, 2016). Bañ on et al (2012aBañ on et al ( , 2012b found that 24% of leaves abscised and leaf area decreased by 48% when V. tinus (laurustinus viburnum) was irrigated with saline solution at an EC of 6.0 dS • m -1 compared with the control (2.0 dS • m -1 ). Callistemon citrinus (red bottlebrush) had a reduction in leaf area of 12% when irrigated with 44 mM NaCl solution (4.0 dS • m -1 ) compared with the control (0.8 dS • m -1 ) ( Alvarez and S anchez-Blanco, 2014).…”
mentioning
confidence: 99%